Human behavioral dynamics and stock return movements: Evidence from China - Peng, Jie (Edelweiss Applied Science and Technology, 2025)
This paper develops an analysis framework based on the principle of human behavior dynamics and the jump-diffusion process. Based on empirical tests on Chinese stock markets, the paper reveals a negative correlation between jump levels in the previous month and stock returns in the following month. On average, an increase of each 1 unit in the value of the jump component results in a lower subsequent stock return of 58 basis points. Moreover, the long-short arbitrage portfolios based on jump levels perform better than the market portfolio; the Sharpe ratio is 4 times that of the market index, indicating that jump-based trading strategies have a great ability to pursue abnormal returns.